Gingerenone A attenuates diabetic vascular remodeling through AMPK/mTOR/S6K1 signaling - Chen, Meixian; Gu, Daqian; Lin, Yi; Zhou, Junwei; Lin, Wansheng; Chen, Zhi; Luo, Zhurong; Chen, Pin (Frontiers in Pharmacology, 2026)
Diabetes accelerates vascular remodeling and contributes to restenosis after revascularization, in part through oxidative stress-driven dysfunction of vascular smooth muscle cells (VSMCs). Gingerenone A (Gin A), a ginger-derived metabolite with reported metabolic activity, has not been examined in the setting of diabetic vascular remodeling. Here we evaluated whether Gin A mitigates high glucose (HG)-induced VSMC dysfunction and neointimal hyperplasia, with emphasis on redox regulation and AMP-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR)/p70 ribosomal S6 kinase 1 (S6K1) signaling. In A10 VSMCs exposed to HG, Gin A reduced proliferation and migration and improved redox status. This was reflected by lower intracellular reactive oxygen species (ROS) and malondialdehyde (MDA), reduced NADPH oxidase 4 (NOX4) expression, and partial restoration of total antioxidant capacity and superoxide dismutase activity. Gin A increased AMPK phosphorylation while suppressing mTOR/S6K1 activation under HG stimulation. AMPK dependence was supported by two perturbation approaches. Compound C attenuated the antiproliferative and anti-migratory effects of Gin A and diminished its effects on mTOR/S6K1 signaling. Additionally, siRNA-mediated knockdown of AMPKα in primary human aortic smooth muscle cells (HASMCs) attenuated the antiproliferative effect of Gin A and blunted the Gin A-associated increase in phosphorylated AMPK. In primary HASMCs, iso-osmotic L-glucose and D-mannitol controls did not reproduce the HG-induced proliferative phenotype, indicating glucose-specific stimulation. In a diabetic rat carotid balloon injury model, oral Gin A attenuated neointimal hyperplasia (reduced intima-to-media ratio), reduced vascular proliferation markers, improved redox indices (lower MDA and higher total antioxidant capacity), and enhanced arterial AMPK activation. In pharmacokinetic studies, a single 10 mg/kg oral dose yielded a maximum plasma concentration (Cmax) of 0.0500 ± 0.0041 μg/mL, a time to Cmax (Tmax) of 0.29 ± 0.10 h and a terminal half-life of 12.41 ± 4.82 h. A 14-day repeat-dose study revealed no overt biochemical or histopathological toxicity under the tested conditions. Together, these data suggest that Gin A limits diabetic neointimal hyperplasia and VSMC dysfunction through an AMPK-dependent mechanism converging on mTOR/S6K1, accompanied by improved redox homeostasis, and support further evaluation of exposure-response relationships and longer-term safety.